Interactive Methods in Organizing English Classes in Secondary Schools - Mingboyeva Muborakxon Nabiyevna (Global Scientific Publishing, 2023)
Today, the younger generation is increasingly interested in learning foreign languages. Therefore, teaching a foreign language, including English, in secondary schools requires the use of interactive methods in the classroom. This article focuses on the effectiveness of organizing lessons using interactive methods in English classes in secondary schools.
Keywords: method; interactive method; information and communication technologies